PEMBELAJARAN TOUR GUIDING: DESKRIPSI CERITA OGOH-OGOH BERBAHASA INGGRIS SEBAGAI DAYA TARIK PARIWISATA BUDAYA - Md. Yudyantara Risadi (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2021)
Tour guiding is one of the school subjects’ to be taught in school, especially for students who enroll in tourism school. This subject gives knowledge to be a good tour guide and be the leader of the improvement of good tourism aspect in a country. To be a good tour guide, it is a must to have knowledge in every aspect of tourism, one of them is cultural tourism. Cultural tourism can be seen in many countries, especially Bali (one of the destination places in Indonesia) that has many cultures within it, such as ogoh-ogoh that become one attraction for domestic and non-domestic tourists. This study aims at finding the appropriate technique of teaching in tour guiding subject with item “Description of ogoh-ogoh’s story”. The method of this research is qualitative method with observation, interview, and documentation as the data collection and library research as the supporting data to complete the primary data. The informantsused in this research were purposively determined. This study is able to help teachers to find out how they teach the students with appropriate technique. Based on the findings, it can be concluded that the description of ogoh-ogoh’s story can be found properly by interviewing the architects of the ogoh-ogoh in order to find out the sotry in more details. The theme of ogoh-ogoh’s story can be in many forms, such as evil, monster, or sometimes God (its manifestation) againsts evil or demons. After finding how to get the story in details, then these stories must be delivered in the classroom in a specific technique, one of the techniques that can beused in the classroom is story telling. This technique is appropriate because it gives a natural way to deliver the story and the information can be interactively received by tourists. This technique has 5 stages, 1) focusing on finding the story of ogoh-ogoh(item of teaching), 2) focusing on the readiness of the students, 3) giving background knowledge to the students and asking them to read the story with their own expression, 4) focusing on how they students become the tour guide telling the story of ogoh-ogohwith their own expression, and 5) focusing on giving feedbacks in order to give additional knowledge to the students.